On the relation between explosive cyclones affecting Europe and the North Atlantic oscillation - Gómara, Iñigo; Rodríguez-Fonseca, Belén; Zurita-Gotor, Pablo; Pinto, Joaquim G (Geophysical Research Letters, 2014)
Intense winter cyclones often lead to hazardous weather over Europe. Previous studies have pointed to a link between the North Atlantic Oscillation (NAO) and strong European windstorms. However, the robustness of this relation for cyclones of varying intensities remains largely unexplored. In this paper, the bi-directional relation between the NAO and cyclones impacting Europe is analyzed for the period 1950–2010 focusing on the sensitivity to storm intensity. Evidence is given that explosive (EC) and non-explosive cyclones (NoEC) predominantly develop under different large-scale circulation conditions over the North Atlantic. Whereas NoEC evolve more frequently under negative and neutral NAO phases, the number of EC is larger under a positive NAO phase, typically characterized by an intensified jet toward Western Europe. Important differences are also found on the dynamics of NAO evolution after peak intensity for both cyclone populations.